Quality assessment of compost produced from agricultural wastes: Impact on the growth and yield of Zea Mays L. - Francisca Okoli; Edna Chukwura; Augustine Mbachu (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Maize (Zea mays L.) is a major crop grown and consumed in Nigeria but poor soil quality has resulted in low yield. This study assessed the quality of compost produced from agricultural wastes and its impact on the yield of Zea mays L.Method The composting process was carried out on a windrow (2 m × 1 m × 1.5 m) in a portion of land beside the Department of Applied Microbiology and Brewing Laboratory, Nnamdi Azikiwe University, Awka. Microbial plate count and isolation were done and various physicochemical parameters were used to assess the quality of the compost. Different combinations of compost and soil were used to determine the growth parameters of Zea mays L. Data was analyzed using SPSS software.Results Microbiological analysis revealed the presence of several bacterial and fungal genera in the compost piles. Temperature increased at the initial phase of composting and decreased towards the end of the composting period. pH increased from 6.7±0.1 to 8.2±0.1 while C: N ratio decreased from 22.5±0.6 to 14.3±0.9. Similarly, there was a decrease in moisture content, organic carbon and total nitrogen from 57±1.0% to 36±1.0%, 45±1.0% to 24.3±0.6% and 2.0±0.1% to 1.7±0.1% respectively, during the composting period. The plant height, number of grains and weight of cob were significantly higher (p < 0.05) in the 100% compost and 75/25% compost/soil treatment when compared to those of the control without compost.Conclusion Compost produced in this study contained microorganisms, nutrients and minerals, which improved the yield of Zea mays L.